Water Use Efficiency in Pineapple Plants Fertilization Based on Water Balance Analysis - Astuti, Nungki Kusuma; Nur Rahman Putra, Rinaldi; Br Saragih, Yuni Arda (Agromet, 2025)
Most fertilization in pineapple cultivation occurs through foliar application, which involves dissolving fertilizers in water and spraying them on the pineapple plants. The provision of irrigated water to plants refers to water balance analysis, which corresponds to the available water supply. The research aims to determine the effect of various foliar volumes on the growth and production of pineapple plants. The research was carried out in April 2022 - July 2023 at PT. Great Giant Pineapple Lampung using a Completely Randomized Block Design (CRBD). We applied four treatments of foliar water, which comprised of 1500 l/ha, 2000 l/ha, 3000 l/ha (as control), and based on water balance analysis. The treatment has three replication each. The results showed there was not significant different of growth and yield between treatments of water balance approach and the 3000 l/ha foliar water volume (control), in which both have reduced water usage by 22% for one cycle of pineapple cultivation. The findings provide a more efficient water manage-ment strategy for foliar fertilization, reducing water usage without affecting plant performance, and supporting sustainable agricultural practices in pineapple cultivation. Further, the findings can serve as a reference for optimizing irrigation scheduling and input costs in large-scale plantations.